Prevalence and clinical characteristics of secondary hypertension in young hypertensive tertiary care patients - Vesamo, Jasmin; Niiranen, Teemu J.; Suvila, Karri (Springer Science and Business Media LLC, 2026)
Current European guidelines recommend screening <30-year-old hypertensive patients for secondary hypertension, but the evidence behind this recommendation is limited. Our objective was to assess secondary hypertension prevalence and etiology among young adults and to determine the characteristics linked with secondary hypertension in these patients. We retrospectively studied 243 Finnish hypertensive adults aged 16-30 years (mean age 25.5 years; 49% women) evaluated at a tertiary care hospital in Finland between 2002 and 2023. Data were collected from electronic health records. Patients were classified under three hypertension subtypes: primary, secondary, or exogenic hypertension. We examined the association between participants characteristics and hypertension subtype (primary versus secondary) using logistic regression. A total of 133 patients had primary hypertension, while 98 patients had secondary hypertension. The most common causes of secondary hypertension were renal disease (n = 77) and sleep apnea (n = 13), whereas other causes were limited to 1-2 cases. Individuals with diabetes mellitus had odds of 2.79 (95% confidence interval [95% CI], 1.21-6.43; P = 0.02) for having secondary versus primary hypertension. A plasma creatinine increase of 1 mmol/l was associated with 1.03-fold (95% CI 1.01-1.04; P = 0.002) odds of secondary hypertension. Apart from renal disease and sleep apnea, other forms of secondary hypertension are extremely rare in young adults with hypertension. In this population, renal parenchymal disease and diabetes mellitus emerged as the most important risk factors for secondary hypertension. Extensive universal screening for secondary hypertension without suspicion of such condition for all hypertensive patients <30 years may be unnecessary.